Informatyczna organizacja projektowa jako organizacja ucząca się : ujęcie modelowe - Dyczkowski, Mirosław (IT-project's organization as a learning organization : the model approach, 2005)
The article presents the model approach to the implementation of the learning organization (LO) concept in IT project teams. The first part briefly characterizes the role of knowledge-based management in IT-project’s organizations. The next part describes fundamentals of LO. Then the author presents the integrated OADI-SMM model of learning processes, based on the idea introduced by Kim. The last part provides the reader with examples of key user learning during ERP systems implementation projects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 87-99